2018
DOI: 10.1002/clc.22953
|View full text |Cite
|
Sign up to set email alerts
|

Association between B‐type natriuretic peptide and within‐visit blood pressure variability

Abstract: Background Blood pressure variability (BPV) has been shown to predict cardiovascular events. Within‐visit BPV is the simplest and easiest measure of BPV, but previous studies have shown conflicts as to whether within‐visit BPV correlates with target organ damage. We aimed to evaluate whether within‐visit BPV correlates with B‐type natriuretic peptide (BNP) in a general population. Hypothesis Within‐visit BPV correlates with BNP in a general population. Methods This was a cross‐sectional study that included 633… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The mechanism by which BPV may be associated with atrial EMD in the setting of STEMI is not clearly understood. However, in STEMI patients, increased LAVi, diastolic dysfunction, and left atrial remodeling may be associated with elevated brain natriuretic peptide due to increased wall tension – a finding that may be associated with both atrial fibrillation [22] and BPV [23].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which BPV may be associated with atrial EMD in the setting of STEMI is not clearly understood. However, in STEMI patients, increased LAVi, diastolic dysfunction, and left atrial remodeling may be associated with elevated brain natriuretic peptide due to increased wall tension – a finding that may be associated with both atrial fibrillation [22] and BPV [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a rule such as X➔Y, in the AC, the Y must be a class attribute. Empirical studies [3], [13] showed that AC often builds more accurate classification systems than traditional classification techniques. Moreover, unlike neural networks [20], which produce classification models that are hard to understand or interpret by end-users, the AC generates rules that are easy to understand and manipulate by end-users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many approaches have been adopted in the AC rule discovery [24]- [26], the FP-growth approach [27], and algorithms such as CPAR [16] that uses a greedy strategy presented in FOIL [10]. To conclude, the AC algorithms [3], [15] extends tid lists intersections methods of vertical association rule data layout [28] to solve classification benchmark problems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations